Dimensionless modeling of fine material distribution in an experimental silo during central spout loading. (January 2023) - Zare, Dariush; Nourmohamadi-Moghadami, Arash; Panigrahi, Shubham Subrot; Karim, Azharul; Singh, Chandra B.
Abstract: Spout loading results in the accumulation of broken kernel and fine materials below the auger chute with spatial distribution over the radial direction. This hinders the air distribution affecting the proper execution of stored grain management practices with any stored bulk. For their optimal performance, it is necessary to assess the effect of systems characteristics on the fine material distribution. This study investigated a generalized dimensionless model of broken corn and foreign material (BCFM) distribution using the dimensionless analysis of the Buckingham theorem. The model considered practical loading parameters in the proposed equation to predict BCFM after the filling process. Practical filling parameters that were investigated includes fill pipe diameter, material flow rate and initial BCFM. Statistical parameters such as RMSE (root mean square error), Chi-square (χ 2 ), coefficient of determination (R 2 ), and MRDM (mean relative deviation modulus) were determined to assess the suitability of the developed model. The results showed that the generalized dimensionless model predicted fine material distribution in the experimental silo with reasonable accuracy. It predicted the nonlinear sifting effect across the radial direction and showed a higher concentration of fines near the bulk core section. It was observed that the sifting effect in a center-filled silo was more pronounced with a lower broken kernel. Highlights: The effective parameters of BCFM (broken corn and foreign material) distribution in filling of a silo were identified. Using dimensional analysis of Buckingham Theorem, the dispersal of fine particles in a small-scale silo were modeled. A dimensionless model of BCFM distribution was developed and validated to be used for grain filling of on-farmsilos.